2007
DOI: 10.1029/2006jf000572
|View full text |Cite
|
Sign up to set email alerts
|

Wind waves in shallow microtidal basins and the dynamic equilibrium of tidal flats

Abstract: [1] Shallow microtidal basins are characterized by extensive areas of tidal flats that lie within specific ranges of elevation. These landforms are inherently flat and their evolution strongly depends on the balance between sedimentary and erosive processes. Here we present a stochastic point model for tidal flat evolution to study the influence of tidal currents and wind waves on tidal flat equilibrium. The model accounts for sediment deposition and sediment resuspension by wind waves and is applied to the Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 30 publications
7
80
0
Order By: Relevance
“…These findings confirm the findings by Davidson-Arnott et al (2002), who stated that not only a large input of SSC (by large river discharges) is required for large amounts of sediment deposition but also a low wave activity. Van der Wal and Pye (2004), Möller (2006), Fagherazzi et al (2007), Delgado et al (2013), andFagherazzi et al (2013) showed that wind wave related shear stress is decreased by vegetation and topographic irregularities. In our study, this effect was reflected in a decrease in observed sediment export from the Kleine Noordwaard study area under conditions of moderately north and easterly winds at low river discharges, since the tidal flats in the north and east of the Kleine Noordwaard area are characterised by a relatively irregular topography due to vegetated remnants of old embankments and polder drainage ditches.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm the findings by Davidson-Arnott et al (2002), who stated that not only a large input of SSC (by large river discharges) is required for large amounts of sediment deposition but also a low wave activity. Van der Wal and Pye (2004), Möller (2006), Fagherazzi et al (2007), Delgado et al (2013), andFagherazzi et al (2013) showed that wind wave related shear stress is decreased by vegetation and topographic irregularities. In our study, this effect was reflected in a decrease in observed sediment export from the Kleine Noordwaard study area under conditions of moderately north and easterly winds at low river discharges, since the tidal flats in the north and east of the Kleine Noordwaard area are characterised by a relatively irregular topography due to vegetated remnants of old embankments and polder drainage ditches.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the system's history is also required to determine if the system is in stable or unstable equilibrium. Second, there is a practical issue of scale in a system with potential alternative stable states: At different locations characterized by the same environmental conditions the system can simultaneously display different states (e.g., tidal marsh, tidal mudflat, or subtidal platform; [40][41][42][128][129][130][131][132]) as a result of locally different histories (e.g., historical disturbance, or historical rate of change of environmental conditions). Together, to adequately document multiple stable states in coastal wetlands, we require observations that broadly span both time and space and, preferably, are also of high temporal frequency and high spatial resolution.…”
Section: Significance Of Multiple Stable States In Observation and Mamentioning
confidence: 99%
“…A first set of morphodynamic models has focused on state bifurcations between tidal basins and mudflats. In these models, alternative states are simulated via physics-based feedbacks between water depth, wave-induced shear stress, sedimentation and erosion [128][129][130]. The key characteristic of these models is to prescribe wave-induced bottom erosion as a function of water depth, with maximum potential erosion at an intermediate water depth.…”
Section: Numerical Modeling Of Multiple Stable States In Coastal Wetlmentioning
confidence: 99%
“…Wind waves and tidal currents are ideal processes for sediment resuspension and transport in areas adjacent to salt marshes. Waves are particularly effective in remobilizing sediments on tidal flats, where shallow water depths result in large wave-induced bottom shear stresses (Carniello et al 2005;Fagherazzi et al 2007). Measurements along the muddy Louisiana coastline show that the concentration of sediments entering a marsh channel is proportional to the significant wave height in the bay in front of the channel (Fagherazzi and Priestas 2010; see Figure 5A).…”
Section: Sediment Fluxes In Tidal Channelsmentioning
confidence: 99%